Ricochet [videorecording (DVD)] - Washington, Denzel, 1954-; Lithgow, John, 1945-; Ice-T (Musician); Pollak, Kevin, 1958-; De Souza, Steve; Silver, Joel; Levy, Michael (Film producer); Mulcahy, Russell, 1953- (HBO Video, 1998)
Rookie cop Nick Styles' arrest of a ruthless psychotic killer, Blake, makes him a deadly enemy. Blake escapes from jail, faking his own death, and starts an intricate plan of revenge involving intimidation, public humiliation and murder. Nick, now the assistant district attorney, is forced to return to the tough streets of his childhood and call on his old friend Odessa, a hustler and drug dealer, for help. Together they set a trap that pits Nick against the killer in a confrontation that will leave only one man alive and victorious.